Pengaruh Kebijakan Dividen dan Kebijakan Utang terhadap Nilai Perusahaan pada PT Sumber Alfaria Trijaya Tbk Tahun 2015-2024 - Pasaribu, Yuliana Boru; Noryani, Noryani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of dividend policy and debt policy on company value. This study uses secondary data from the financial statements of PT Sumber Alfaria Trijaya TBK listed on the Indonesia Stock Exchange (IDX) for 2015-2024. The data analysis method used is multiple linear regression with the help of Statistical Package for the Social Sciences (SPSS) version 22 software. The partial results of the study indicate that there is one variable, namely dividend policy (DPR), which shows no effect on company value, this is indicated by the calculated t-value <t-table (-1.709 <2.364) and the significance level obtained is 0.131 with a significant level greater than the significance level of 0.05. While one variable, namely Debt Policy (DER), has a significant positive effect on company value, this is indicated by the calculated t-value>t-table (3.228>2.364) and the significance level of 0.014 is smaller than the significance level of 0.05. The results of this simultaneous study indicate that Dividend Policy and Debt Policy jointly influence Firm Value, as evidenced by the calculated F-value > F-table (5.257 > 4.737), with a significance level of 0.040, which is lower than the required level of 0.05. The predictive power of these two variables on Firm Value is 28.7%, as indicated by the adjusted R-square of 28.7%. The remaining 71.3% is influenced by other factors not included in this study.